Features of Diagnosis and Surgical Treatment of Abdominal Aortic Aneurysms with a Horseshoe Kidney - Ihor I. Kobza; Yuliya S. Mota; Taras I. Kobza (Ukrainian Journal of Cardiovascular Surgery, 2022)
Introduction. Reconstructive surgery of abdominal aortic aneurysms, despite significant international experience, remains one of the most complex issues of current vascular surgery, especially due to anatomical variability of arterial blood supply of the kidneys and abnormalities in their development, among which the most common is a horseshoe kidney. Features of vascularization, placement of the renal isthmus relative to the main vessels, the choice of the optimal method of abdominal aortic aneurysm reconstruction cause a high risk of surgery. The issues of open and endovascular aortic grafting, possibility of crossing the isthmus of the horseshoe kidney, feasibility of reconstruction of additional renal arteries still remain controversial.The aim. Improvement of the diagnosis and surgical treatment of abdominal aortic aneurysms with a horseshoe kidney.Case presentation. In our observation, in a 61-year-old patient, by clinical examination, laboratory and diagnostic imaging the diagnosis of two infrarenal abdominal aortic aneurysms with a horseshoe kidney was confirmed, that has become a direct indication for surgical intervention: exclusion of infrarenal aortic aneurysms from the blood flow, abdominal aortic prosthetic grafting with reimplantation of the renal isthmus arteries into the prosthetic graft. This clinical case confirms the advantages of open surgical technique, using transperitoneal approach, which not only provided sufficient exposure of the operating area, but also allowed to perform optimal reconstruction of the abdominal aorta without crossing the functioning isthmus of the horseshoe kidney with preservation of blood flow through additional renal arteries.Conclusion. Careful preoperative assessment of the peculiarities of the blood supply of the horseshoe kidney with coexistent abdominal aortic aneurysms allows to optimize the tactics of surgical treatment, prevent the development of severe complications and achieve complete recovery of the patient.